1972
DOI: 10.1161/01.res.30.6.651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrasystoles on Idioventricular Rhythm

Abstract: Ventricular extrasystoles exert a variable effect on idioventricular rhythm. The postextrasystolic, or the "returning," cycle may be unchanged, or it may be shorter or longer than the dominant cycle. The factors responsible for these different responses have never been investigated. Therefore, the effect of electrically induced extrasystoles was studied by microelectrode techniques in an in vitro model of idioventricular rhythm consisting of spontaneously firing Purkinje fiber bundles with their attached ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Addition of a net outward current of <1 ,gA/cm2 would convert the system, via a saddle-node bifurcation, into one containing three equilibrium points. In that circumstance, very long prolongations of cycle length showing oscillatory activity in the pacemaker range of potentials similar to those experimentally seen in Purkinje fiber (Klein et al, 1972;Antzelevitch and Moe, 1983) and in heart cell aggregates (Guevara et al, 1986) would then result if the new equilibrium point in the pacemaker range of potentials were to be unstable and have at least one pair of complex conjugate eigenvalues (see also Clay et al, 1984;Reiner and Antzelevitch, 1985).…”
Section: Tolementioning
confidence: 70%
See 2 more Smart Citations
“…Addition of a net outward current of <1 ,gA/cm2 would convert the system, via a saddle-node bifurcation, into one containing three equilibrium points. In that circumstance, very long prolongations of cycle length showing oscillatory activity in the pacemaker range of potentials similar to those experimentally seen in Purkinje fiber (Klein et al, 1972;Antzelevitch and Moe, 1983) and in heart cell aggregates (Guevara et al, 1986) would then result if the new equilibrium point in the pacemaker range of potentials were to be unstable and have at least one pair of complex conjugate eigenvalues (see also Clay et al, 1984;Reiner and Antzelevitch, 1985).…”
Section: Tolementioning
confidence: 70%
“…At low pulse amplitudes, there are two different well-separated ranges of tc, over which prolongation can be seen, with the first (Fig. 3, middle; arrow labeled a) being due to prolongation of action potential duration (Klein et al, 1972;Jalife and Moe, 1976) and the second (Fig. 3, middle; arrow labeled b) being due to prolongation of the duration of diastole (Weidmann, 1951;Jalife and Moe, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy of Precordial Percussion Pacing idioventricular rhythm, of which automaticity usually originated from the pacemaker cells in the His-Purkinje system. 22 In addition, the width and amplitude of the QRS complex during PPP, as well as ventricular electrical pacing, were greater than those during the sinus rhythm, as shown in Figure 4. Thus, PPP may have induced the electrical activity in the ventricular contractile myocardium rather than the cardiac conduction system.…”
Section: Experiments 2: Analysis Of Waveforms Of the Developed Arteriamentioning
confidence: 90%
“…Klein et al 3 reported on the effects of "extrasystoles" on the return cycle of automaticity in isolated canine Purkinje fibers. They found that premature action potentials elicited during the late stages of repolarization usually produced a shortened "return cycle" (the interval from the upstroke of the premature impulse to the upstroke of the subsequent, or returning, automatic beat) in fibers with normal maximum diatolic potentials "because of the marked abbreviation of the duration of the [premature] action potential."…”
mentioning
confidence: 99%